Gambaran Pengetahuan dan Sikap Keluarga tentang Attention Deficit Hyperactivity Disorder (ADHD) pada Anak - Ni Made Candra Dewi Sudana; I Made Sudarma Adiputra (Jurnal Akademika Baiturrahim Jambi, 2023)
Lack of information obtained by families about the basic concepts, treatment, signs and symptoms of ADHD in children causes family knowledge about ADHD to be severely lacking. Because of this, children who have signs and symptoms of ADHD such as hyperactive behavior tend to be difficult to distinguish because most parents consider it a natural thing. This study aims to see an overview of the level of knowledge and family attitudes about Attention Deficit Hyperactivity Disorder (ADHD) in children. The research design used was descriptive quantitative with a total sample of 113 families. The sampling technique uses multistage random sampling. The results of the study for knowledge showed that out of 113 respondents, 103 respondents (91.25) had insufficient knowledge, 6 respondents (5.3%) had sufficient knowledge and 4 respondents (3.5%) had good knowledge about ADHD in children. As for attitudes, it shows that as many as 56 respondents (49.6%) have a good attitude, 55 respondents (48.7%) have sufficient attitudes, and 2 respondents (1.8%) have less attitudes. It can be summarized that in this study, most families have less knowledge and are inversely proportional to most have a good attitude about ADHD in children